Placelessness of urban design and industrial branding in small town planning. Issue 4 (4th July 2021) - Kortelainen, Jarmo; Albrecht, Moritz
ABSTRACT: The paper analyses placemaking in a small Finnish single-industry town through two architectural projects: the municipality's downtown rejuvenation plan and the new visitor centre of a transnational corporation. It deploys Relph's concept of placelessness interpreting it relationally with the concept of assemblage, and analyses how the two projects resonate with the place's material and expressive elements. They represent high-quality architecture but embody placelessness: the visitor centre is physically detached from the town, and the downtown plan neglects industrial heritage. This is a missed opportunity for attractive place-making, and shows an urge for novel public-private collaboration in small town urban design.